SEEKING THE PUBLIC INTEREST: SURVEY KEBUTUHAN MASYARAKAT TINGKAT KECAMATAN SEBAGAI BAHAN MASUKAN BAGI PERENCANAAN PEMBANGUNAN DI KOTA SERANG - Prafitri, Nikki Prafitri (Majalah Ilmiah Dinamika Administrasi (MIDA), 2024)
Seeking the public interest is an effort to involve the community in the development process so that the programs carried out by the government are in line with the needs of the community. The form of applying this principle is to conduct a survey of community needs as input for development planning in Serang City. This survey is also a manifestation of efforts to implement planning with a bottom-up model, starting from conducting a needs survey at the sub-district level in Serang City. This research method is using quantitative method. The results show that the average priority of community needs at the sub-district level is in sub-affairs such as coaching and assistance for micro and small businesses, the formation of cooperatives, women's empowerment, handling beggars, handling juvenile delinquency, handling child labour, procurement and maintenance of Public Street Lighting (PJU), construction and maintenance of drainage and waste management through the procurement of Landfill (TPS). Thus, development planning needs to be directed to efforts to realize development programs that are in line with the priorities of these needs.